2023
DOI: 10.3390/ijms241813921
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Foxg1 Delayed Myelination during Early Postnatal Brain Development

Guangliang Cao,
Congli Sun,
Hualin Shen
et al.

Abstract: FOXG1 (forkhead box G1) syndrome is a neurodevelopmental disorder caused by variants in the Foxg1 gene that affect brain structure and function. Individuals affected by FOXG1 syndrome frequently exhibit delayed myelination in neuroimaging studies, which may impair the rapid conduction of nerve impulses. To date, the specific effects of FOXG1 on oligodendrocyte lineage progression and myelination during early postnatal development remain unclear. Here, we investigated the effects of Foxg1 deficiency on myelin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Our data demonstrated that in the cerebral cortex of 31-day-old opossums, the morphology of astrocytes was similar to that of mice [52]. Olig2, which is a transcription factor involved in the differentiation of oligodendrocytes and neurons, plays a crucial role in the specification and differentiation of astrocytes in cerebral white matter during development [53][54][55]. A lineage analysis of Olig2-expressing cells using a tamoxifen (TAM)-inducible Cre/loxP system showed that Olig2+ progenitors give rise to astrocytes at a late embryonic stage.…”
Section: Discussionsupporting
confidence: 57%
“…Our data demonstrated that in the cerebral cortex of 31-day-old opossums, the morphology of astrocytes was similar to that of mice [52]. Olig2, which is a transcription factor involved in the differentiation of oligodendrocytes and neurons, plays a crucial role in the specification and differentiation of astrocytes in cerebral white matter during development [53][54][55]. A lineage analysis of Olig2-expressing cells using a tamoxifen (TAM)-inducible Cre/loxP system showed that Olig2+ progenitors give rise to astrocytes at a late embryonic stage.…”
Section: Discussionsupporting
confidence: 57%